The courtroom as an affective arrangement: analysing atmospheres in courtroom ethnography. Issue 3 (2nd September 2018) - Bens, Jonas
Abstract: This article proposes a methodological approach to courtroom ethnography by developing the idea of the courtroom as an affective arrangement. In the courtroom, humans and their linguistic utterances, but also material objects and infrastructures, visuals, voices, and sounds are relationally entangled. This is the analytical entry point for ethnographically describing the atmosphere of a court proceeding without reducing atmosphere either to the result of courtroom talk or to the emotional experiences of the participants. For a thick ethnographic description of courtroom atmospheres, the ethnographer should point out how all kinds of different bodies perform in the theatre of power that is a court proceeding.